Booking.com customer based equity model case study what motivates customers to use booking.com besides the online rates? - Azevedo, Catarina Torres Pinto De (2020)
The present work studied the brand equity of Booking.com following the Keller’s Customer Based Brand Equity model. Booking.com is one of the main players within the Online Travel Industry, in particular the Online Travel Agencies, which is why it was chosen for an analysis to understand the perception of the customers towards a very well-known brand. The analysis was performed using the Keller’s Customer Based Brand Equity Pyramid based on the results obtained from a qualitative interview of 12 Portuguese people and a quantitative survey of 120 people in the Portuguese market. The results of the analysis showed that the brand has a high salience but there are some possible opportunities to build a stronger position in the mentioned market in terms of Brand Responses andRelationships.